2016
DOI: 10.1080/01694243.2016.1179824
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic polygonal spreading of a droplet on a lyophilic pillar-arrayed surface

Abstract: We experimentally investigated the dynamic polygonal spreading of droplets on lyophilic pillar-arrayed substrates. When deposited on lyophilic rough surfaces, droplets adopt dynamic evolutions of projected shapes from initial circles to final bilayer polygons. These dynamic processes are distinguished in two regimes on the varied substrates. The bilayer structure of a droplet, induced by micropillars on the surface, was explained by the interaction between the fringe (liquid in the space among the micropillars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…The droplets in Raj et al 22 demonstrated finite contact angles in the nonpropagating regime and allowed superior control over fluidic manipulation. Similar shapes in the thin-film regime or directional spreading have been previously demonstrated on microdecorated surfaces, 23 lyophilic pillararrayed surfaces, 24,25 and chemically patterned micropillar surfaces 26,27 as well. Similarly, droplets with polygonal contact line can also be obtained by varying the concentration of a binarymixture on a microdecorated substrate.…”
Section: ■ Introductionsupporting
confidence: 81%
“…The droplets in Raj et al 22 demonstrated finite contact angles in the nonpropagating regime and allowed superior control over fluidic manipulation. Similar shapes in the thin-film regime or directional spreading have been previously demonstrated on microdecorated surfaces, 23 lyophilic pillararrayed surfaces, 24,25 and chemically patterned micropillar surfaces 26,27 as well. Similarly, droplets with polygonal contact line can also be obtained by varying the concentration of a binarymixture on a microdecorated substrate.…”
Section: ■ Introductionsupporting
confidence: 81%
“…Similar to the way it influences spontaneous spreading (see, for example, the elegant studies in ref 46,47), it should also influence spontaneous triple line retraction, namely work of adhesion measurements. As in other wetting properties, it is expected to depend on whether the roughness results in a Wenzel or in a Cassie regime.…”
Section: ■ Results and Discussionmentioning
confidence: 84%
“…Surface roughness plays a significant role in wetting phenomena. Similar to the way it influences spontaneous spreading (see, for example, the elegant studies in ref , ), it should also influence spontaneous triple line retraction, namely work of adhesion measurements. As in other wetting properties, it is expected to depend on whether the roughness results in a Wenzel or in a Cassie regime. , It is expected that a Wenzel regime will result in a higher work of adhesion, while Cassie regime will result in a lower work of adhesion.…”
Section: Resultsmentioning
confidence: 86%
“…The higher aspect ratio of the droplets on ME is also consistent with the formation of filaments droplet on the grooves. 30 Although the roughness measured from AFM images was only 3.3 nm in RMS, the boundary of the oil nanodroplets in the solution of pH 3.0 was clearly pinned along the layers of MoS 2 edge. It is remarkable that the layered nanostructure of MoS 2 edge surface is already sufficient to lead to pronounced effects on the formation and morphology of nanodroplets.…”
Section: ■ Experimental Sectionmentioning
confidence: 95%